Dual-tasking in older women: physical activity or else?. (2nd January 2022) - Muhaidat, Jennifer; Al-Yahya, Emad; Mohammad, Maha T.; Qutishat, Dania; Okasheh, Rasha; Al-Khlaifat, Lara; Lawrie, Sophie; Esser, Patrick; Dawes, Helen
ABSTRACT: The interplay between gender, Physical Activity (PA), and Dual Tasking (DT) in older adults is unclear. This study aimed to address DT based on gender and PA level. One-hundred and twenty older adults (81 women and 39 men) participated. Timed up and go test and spatiotemporal gait measures were collected in single and DT conditions. Participants were grouped according to gender and PA level. Physical activity did not explain gender differences, women were slower and had shorter stride lengths when DT regardless of PA level. Findings indicate the necessity for tailored PA and functional interventions to improve women's performance.